Distribution of Dengue Hemorrhagic Fever (DHF) Cases in South Sumatra Province, Indonesia: Descriptive Analysis from 2018 to 2022 - Suci Rahmadani; Syela Christy Janri; Sani Zahra; Sartika; Resyanti Glorya Lestari (Journal of Epidemiology and Health Science, 2025)
Background: The increase in cases and mortality rates due to Dengue Hemorrhagic Fever (DHF) from year to year requires systematic monitoring of epidemiological trends as a basis for formulating effective public health policies. Objective: This study aims to describe the trend of DHF cases in South Sumatra Province during the period 2018–2022, provide an overview of the epidemiology of the disease, and determine the priorities for public health interventions. Method: This study uses a quantitative descriptive approach by utilizing secondary data obtained from the South Sumatra Provincial Health Profile. Data collection was carried out through a documentation study of morbidity rates, mortality rates, and distribution of DHF cases by district/city. Data analysis was carried out descriptively using tables and graphs to identify patterns of occurrence. Results: The analysis results show fluctuations in the incidence of DHF with a peak Incidence Rate (IR) of 33 per 100,000 population in 2019 and 2022. The highest Case Fatality Rate (CFR) was recorded in 2018 and 2022 at 1.1%, respectively. This trend variation is thought to be influenced by changes in climate conditions, community behavior, and vector resistance to the insecticides used. Conclusion: DHF is still a significant health problem in South Sumatra Province. Therefore, it is necessary to strengthen prevention efforts through interventions that focus on changing community behavior, improving the environment, and sustainable vector control to reduce the incidence and mortality due to DHF.